PENGEMBANGAN KOMIK DIGITAL TERINTEGRASI TRI KAYA PARISUDHA PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU SISWA SMA DI KABUPATEN BULELENG - Ari Diasih, Ni Made; Darma, I Wayan Wira; Ayu, Putu Eka Sastrika (Guna Widya: Jurnal Pendidikan Hindu, 2026)
The low availability of innovative learning media based on local wisdom, especially in the material of Hindu religious heritage in Asia, is the main basis for conducting this research. Therefore, this research aims to (1) describe the prototype of the Tri Kaya Parisudha integrated digital comic; (2) test the validity; and (3) measure and describe the practicality of the Tri Kaya Parisudha integrated digital comic in the Hindu religious education subject for high school students in Buleleng Regency. The study design is a Research and Development (R&D) development study that adopts the 4-D development model. Tri Kaya Parisudha's integrated digital comic is the subject while the validity and practicality of the developed media are the objects of research. Data collection was obtained from observation, interview and questionnaire methods. Data processing used qualitative and quantitative descriptive techniques. The following are the results of this research: (1) the prototype of the integrated digital comic Tri Kaya Parisudha's integrated digital comic was developed at the design stage including the activities of compiling the story script, characters, storyboard, making comics on Comic.ai, (2) The results of the validation of digital comics in terms of content suitability obtained a validity coefficient of 0.87 with a very high validity category, the presentation quality aspect obtained a coefficient of 0.88 with a very high validity category and the language suitability obtained a validity coefficient of 0.83 with a very high validity level. (3) The assessment of the practicality of digital comics obtained a score percentage from teacher responses reaching 93% which is included in the very practical level and the score percentage from student responses of 90% is in the very practical category. Keywords: Digital comics, Tri Kaya Parisudha, Hindu religious education